2015
DOI: 10.4081/jbr.2015.4916
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age, anatomical site and bone structure on osteogenesis in New Zealand White rabbit

Abstract: Among animal models, rabbits are widely used in medical research, as they fill the gap between smaller models, commonly employed in basic science, and larger ones, which are better suited for preclinical trials. Given their rapid growth, rabbits provide a valuable system for the evaluation of bone implants for tissue regeneration. By means of a histomorphometric analysis, here we quantified the mineral apposition rates (MARs) in osteonic, periosteum and endosteum osteogenic fronts, of skeletal elements within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Rabbit models are often cited as the most common in all musculoskeletal research 84,85 and indeed were the most frequently reported in our systematic review. This is due, in part, to their convenience in terms of size, cost, handling, and relatively young skeletal maturation age of 20–30 weeks 83,87 . Though their small size may be a limiting factor for experimental implants, 3D printing is well‐suited for creating size‐appropriate structures, as evidenced in part by their frequent use for 3DP pTi studies.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit models are often cited as the most common in all musculoskeletal research 84,85 and indeed were the most frequently reported in our systematic review. This is due, in part, to their convenience in terms of size, cost, handling, and relatively young skeletal maturation age of 20–30 weeks 83,87 . Though their small size may be a limiting factor for experimental implants, 3D printing is well‐suited for creating size‐appropriate structures, as evidenced in part by their frequent use for 3DP pTi studies.…”
Section: Discussionmentioning
confidence: 99%
“…New perspectives indicate that the osteoporotic rabbit model derived by ovariectomy or glucocorticoid may be more suitable for studying human postmenopausal osteoporosis ( Zhang et al, 2016 ; Wanderman et al, 2018 ). Rabbit bone has Haversian systems and reaches quick bone maturity at around 6 months ( Permuy et al, 2019 ; Ravanetti et al, 2015 ). Similar to humans, rabbits possess active intracortical remodeling and a faster bone turnover which is favorable for studying compounds that affect bone remodeling balance ( Mapara et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…ey have been studied in various animal models, such as rabbits [5,6,8,27], dogs [3,7,9,15,16], sheep [11], and mini-pigs [10,17,28], and humans as well [4, 13, 14, 18, 19, 21-26, 29, 30]. Among all animal models for medical and dental research, rabbits are widely used [31][32][33].…”
Section: Introductionmentioning
confidence: 99%